A Maritime-Based Fiscal Development Strategy Model in East Kalimantan Province, Indonesia - Irhamsyah; Sutanto Hidayat; Maranatha Wijayaningtyas; Nanta Sigit (International journal of technology and education research, 2025)
This study integrates economic and geospatial approaches to analyze the effectiveness of capital expenditures, fund allocation, and physical monitoring in regional development and improving community welfare, particularly in Kalimantan. This integration aims to provide a more comprehensive understanding of the contribution of fiscal policy to regional development. Fiscal instruments such as the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Regional Original Revenue (PAD) are analyzed to determine the extent to which each impacts regional economic growth and improves the quality of life of the community. In addition to the fiscal aspect, this study also evaluates the use of geospatial technology in monitoring the progress of physical development in the field. This technology was assessed in terms of accuracy, efficiency, and its potential to support real-time development planning and monitoring processes. A quantitative approach was used, applying panel data regression models, Partial Least Squares (PLS) analysis, and spatial analysis to comprehensively describe the relationships between variables. The results of the study indicate that the integration of fiscal and spatial data can provide more accurate and relevant information for decision-making in regional development planning. The combination of these two approaches has been proven to strengthen the effectiveness of development policies and can be used as a reference in developing data-driven, sustainable development strategies that are oriented towards equitable distribution of community welfare.